Crime and the transition to parenthood. The role of sex and relationship context - Christian Weisæth Monsbakken; Torbjørn Skardhamar; Torkild Hovde Lyngstad (Statistics Norway, Research Department, 2012)
Research on desistance from crime has paid little attention to parenthood as a "turning point". In this paper, we use Norwegian register data on a population of men and women who had their first child between 1995 and 2001 (131,167 women and 127,415 men). We provide separate estimates for sex and marital status as parenthood has different implications for men and women. Their social and economic situations will also vary by marital status, which is likely to have implications for offending. We describe the changes in offending for this sample year-by-year, comparing subjects before and after child-birth. Overall, we find that the transition to parenthood is characterized by a decrease in criminal activity. There is considerable heterogeneity between women and men. The term "turning point" applies only to men who are not living with the other parent.
Keywords: J12; K49; 330; parenthood; crime; social control theory; sex; register data; turning points